Modeling Vapor Flow from a Pervaporative Irrigation System. Issue 4 (4th October 2013) - Todman, Lindsay C.; Ireson, Andrew M.; Butler, Adrian P.; Templeton, Michael R.
Abstract : Experimental and modeling results were used to develop a conceptual understanding of the process of pervaporative irrigation in dry soils. When irrigating in this way, a pervaporative membrane is formed into a tube, buried in the soil, and filled with water. If the surrounding soil is dry, a chemical potential gradient across the membrane draws water into the soil. Water can only desorb from the membrane as a vapor, however, so it enters the soil in the vapor phase. This study corroborates previous evidence that vapor flow can significantly affect the flux from the irrigation membrane under arid conditions. A new model of water transport from a pervaporative irrigation membrane in unvegetated soils was developed, taking into account transport in both liquid and vapor phases, and successfully simulated experimental observations of the total water flux, relative humidity, and water content distribution in three soil types. Modeling results showed that the capacity for moisture sorption within different soil types affects both condensation in the soil and the subsequent flux from the pervaporative membrane. A mathematical relationship for the moisture sorption isotherm for a soil can therefore be used to predict the flux across the membrane in that soil. If condensation is significant, liquid flows through the soil also affect the flux from the membrane. Model simulations suggest that the flux from the pervaporative membrane is primarily limited by humid conditions within the soil rather than the transport of water across the membrane, thus plant interactions with the soil conditions should increase the irrigation flux.